Promoting Equity in Market-Driven Education Systems: Lessons from England - Kirstin Kerr; Mel Ainscow (MDPI AG, 2022)
There is a global trend towards the use of market-driven approaches as a strategy for educational reform. However, this is creating new barriers to the promotion of equity in some countries. Focusing on England as an extreme example of this approach, this paper points to some possibilities for addressing this concern. It reports findings from a series of studies in high poverty contexts in England. These studies have typically involved local educational practitioners and university researchers working together in ways designed to support equitable developments. Lessons from these experiences are identified for market-driven systems internationally. They suggest that to create more equitable arrangements, schools need to work together, and with other organizations, both within and beyond their local areas. They also point to the value of surfacing and using the rich experiential and contextualized knowledge held by practitioners to inform these collaborative developments. Acting on these lessons would mark a significant shift for systems whose current emphasis is on schools working competitively and in isolation, often to the detriment of disadvantaged children and young people.